2016
DOI: 10.1155/2016/9421571
|View full text |Cite
|
Sign up to set email alerts
|

MUC1 Immunohistochemical Expression as a Prognostic Factor in Gastric Cancer: Meta-Analysis

Abstract: MUC1, a member of the mucin family, is expressed in tumors of various human organs and may function as an antiadhesion molecule that inhibits cell-to-cell adhesion, inducing tumor metastasis, and served as a potential biomarker of tumor progression in early gastric cancer. However, its prognostic significance in gastric cancer is still in dispute. We performed a meta-analysis to evaluate the relationship between MUC1 expression and prognosis of gastric cancer. A total of ten eligible studies with 834 cases and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 36 publications
1
27
0
1
Order By: Relevance
“…In this study, we further identified MAGEA12 expression as a novel predictor for the outcome of gastric cancers. Currently, several other prognostic markers in gastric cancer such as such as MUC1 have been validated [16], therefore, here we also proposed that combination of MAGEA12 with other factors may add prognostic and classification information for gastric cancers.…”
Section: Discussionmentioning
confidence: 91%
“…In this study, we further identified MAGEA12 expression as a novel predictor for the outcome of gastric cancers. Currently, several other prognostic markers in gastric cancer such as such as MUC1 have been validated [16], therefore, here we also proposed that combination of MAGEA12 with other factors may add prognostic and classification information for gastric cancers.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, MUC1 in tumor cells has been shown to be aberrantly glycosylated, which results in overexpression of several novel tumor-associated carbohydrate structures that can serve as a possible prognostic marker or therapeutic target. A recent meta-analysis of ten translational studies demonstrate that MUC1 immunohistochemical expression is highly correlated with intestinal histology, vascular invasion, nodal metastasis, and decreased survival in gastric cancer patients [37].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, p53 and Ki-67 markers were not found to be associated with tumor recurrence (15) . Other markers are used to understand tumor biological behavior, e.g., mucin expression, through which subclassification of gastric cancer in phenotypes was established (2,7,14,19,49,64,66,69) . Thus, gastric tumors may express mucin phenotypes of gastric, intestinal, and mixed intestinal and gastric, or indeterminate types (10,50) .…”
Section: Discussionmentioning
confidence: 99%